(untitled) (Texto Livre, 2021)
Due to the potential of ICT to enhance the development of reading and writing skills, it has become an emerging field of scientific research. This paper aims examine scientific literature that investigates the use of ICT in the development of writing and reading skills for the years 2010 and 2020 in five databases. A descriptive and quantitative methodology has been followed to present the most important characteristics and results of the 16 selected scientific articles. In analysis of the research findings we explored the most significant bibliometric data and the effectiveness of ICTs in enhancing the writing and reading skill of students. The results confirmed that, despite the fact that scientific production in this field is still underdeveloped, digital technologies can help in the development of reading and writing skills. There is a need to improve teacher training for the effective integration of technologies in both teaching and learning of reading and writing.